TPACK Model Based Instruction in Teaching Writing: An Analysis on TPACK Literacy - Ammade, Salasiah; Mahmud, Murni; Jabu, Baso; Tahmir, Suradi (International Journal of Language Education, 2020)
Acknowledging prior knowledge on technology, pedagogy, and content of lecturers in this early stage of developmental research is assuming important as basic data for further steps in designing TPACK model-based instruction in teaching writing. Therefore, having investigation on TPACK literacy of the lecturers will complete the data needed in this study. This paper presents an analysis of Technological Pedagogical and Content Knowledge (TPACK) literacy among lecturers at Universitas Muhammadiyah Parepare, Indonesia. In finding the data, the TPACK survey of Schmidt, Baran, Thomson (2009) was applied by having little modification on it. The main points on the survey were about Technological Knowledge (TK), Pedagogical Knowledge (PK), Content Knowledge (CK), and TPACK. In gaining the data, the questionnaire as the research instrument was distributed to lecturers in the English Education Department, and their responses were analyzed quantitatively. This research was conducted at Universitas Muhammadiyah Parepare, South Sulawesi province, Indonesia. The questionnaire results showed that the lecturersâ€™ levels of literacy on technology, pedagogy, content knowledge, and TPACK are on moderate stage.Â  They can be categorized as good level on overall TPACK literacy, but need to improve in order to achieve better results by having more practice or learning workshops.